PENGEMBANGAN KETERAMPILAN BERBICARA BAHASA JERMAN MELALUI DISKUSI KELOMPOK - Setiawan, Setiawan (Allemania, 2011)
In the teaching and learning process, the speaking skill of German language is still difficult to master. The fact shows that most learners still rarely use German language either in the classroom situation or in the real life. From the research conducted by Nurhani (2007) it is found that one alternative method of learning which can increase university students’ participation is the interactive method. One of the main features of this method is the group division which divided a group into large and small group. In this group the interaction between students can be increase. Based on that explanation, this research will developed a certain learning model which can increase the German speaking skill of university students. Few important results from this research are as follow: (1) the model is new to the German Department of UPI, (2) after implementing it three times, both lecturers and students are familiar with the situation developed and the discussion become more attractive and conducive in increasing the students skill especially in speaking, (3) the themes provided are still lack of variation and the lecturer roles as the facilitator of the discussion still needed to be developed, (4) this method can increase the students participation in the teaching and learning process, (5) it is recognized that lecturer have to develop a certain strategy in delivering the model of learning in speaking through the discussion technique, (6) by using Einstieg (introduction), the students are not only capable in knowing the coverage of the theme, but they also can identify the vocabulary and also the terms related to the theme. This will make the discussion more dynamic, (7) lecturer at least has to consider three aspects in group division: first the student’s competency, it means that all students with high learning achievement are spread into all group. Second, the time in making the groups. Third the class setting, (8) in the class discussion phase, lecturer must to be able to manage the class situation so that the discussion is not monopolize by few students.